Home oximetry to screen for obstructive sleep apnoea in Down syndrome. Issue 10 (14th May 2018) - Hill, Catherine M; Elphick, Heather E; Farquhar, Michael; Gringras, Paul; Pickering, Ruth M; Kingshott, Ruth N; Martin, Jane; Reynolds, Janine; Joyce, Anna; Gavlak, Johanna C; Evans, Hazel J
Abstract : Objective: Children with Down syndrome are at high risk of obstructive sleep apnoea (OSA) and screening is recommended. Diagnosis of OSA should be confirmed with multichannel sleep studies. We aimed to determine whether home pulse oximetry (HPO) discriminates children at high risk of OSA, who need further diagnostic multichannel sleep studies. Design: Cross-sectional prospective study in a training sample recruited through three UK centres. Validation sample used single-centre retrospective analysis of clinical data. Patients: Children with Down syndrome aged 0.5–6 years. Intervention: Diagnostic multichannel sleep study and HPO. Main outcome measures: Sensitivity and specificity of HPO to predict moderate-to-severe OSA. Results: 161/202 children with Down syndrome met quality criteria for inclusion and 25 had OSA. In this training sample, the best HPO parameter predictors of OSA were the delta 12 s index >0.555 (sensitivity 92%, specificity 65%) and 3% oxyhaemoglobin (SpO2 ) desaturation index (3% ODI)>6.15 dips/hour (sensitivity 92%, specificity 63%). Combining variables (delta 12 s index, 3% ODI, mean and minimum SpO2 ) achieved sensitivity of 96% but reduced specificity to 52%. All predictors retained or improved sensitivity in a clinical validation sample of 50 children with variable loss of specificity, best overall was the delta 12 s index, a measure of baseline SpO2 variability (sensitivity 92%; specificity 63%). Conclusions: HPO screening could halve the number of children with Down syndrome needing multichannel sleep studies and reduce the burden on children, families and health services alike. This approach offers a practical universal screening approach for OSA in Down syndrome that is accessible to the non-specialist paediatrician.